2016
DOI: 10.5455/aim.2016.24.286-292
|View full text |Cite
|
Sign up to set email alerts
|

Teleconsultation and Clinical Decision Making: a Systematic Review

Abstract: Background:The goal of teleconsultation is to omit geographical and functional distance between two or more geographically separated health care providers. The purpose of present study is to review and analyze physician-physician teleconsultations. Method: The PubMed electronic database was searched. The primary search was done on January 2015 and was updated on December 2015. A fetch and tag plan was designed by the researchers using an online Zotero library. Results: 174 full-text articles of 1702 records me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(96 citation statements)
references
References 73 publications
(85 reference statements)
2
80
0
5
Order By: Relevance
“…Telemedicine provides specifi c medical services, including teleconsultation, telemonitoring, teleeducation, telesurgery, teleconference, etc 5 . Telemedicine allows remote monitoring and reassessment, ensuring continuity of day to day care at signifi cantly lower costs than hospitalization.…”
Section: Telemedicine In Europementioning
confidence: 99%
“…Telemedicine provides specifi c medical services, including teleconsultation, telemonitoring, teleeducation, telesurgery, teleconference, etc 5 . Telemedicine allows remote monitoring and reassessment, ensuring continuity of day to day care at signifi cantly lower costs than hospitalization.…”
Section: Telemedicine In Europementioning
confidence: 99%
“…35 Teleconsultation Teleconsultation can be considered as a communication between professionals or a patient and a professional. 45 There is an emerging trend for patients and professionals to search information online. An award-winning teleconsultation portal QA Dental was developed for international professional online consultations.…”
Section: Dental Teleradiologymentioning
confidence: 99%
“…Moreover, they permit access to lab test results, schedule appointments with the doctors and refill prescriptions [71,72]. A systematic review of the effect of patient portals concluded that ten out of the patients located in remote and rural areas [49]. For instance, Alentejo, an underserved region in Portugal with regard to adequate and accessible health care, successfully initiated telemedicine and teleconsultation in 1998 as a means to improve healthcare and is now an essential part of service delivery there [50].…”
Section: Health Portalsmentioning
confidence: 99%